Multi-criteria analysis of machines using AHP - Fernández, Félix (2020)
A comprehensive analysis of the machines is a key aspect that must be considered in any production plant. In this sense, the objective of this paper is to categorize the machines that are part of a beer can packaging line, based on the criticality of each one, through an automated fault recording scheme and the calculation of lost production. An operational investigation has been carried out, in which the data collection has been based on the failures of the machines that compose the production line, and then carried out a descriptive investigation, of an empirical and documentary nature, supported by primary and secondary sources where cases of safety and quality events, which have occurred in similar plants of the same company, during the last two years were studied. On the other hand, it is known that there is a constant technological advance in the industrial sector and an increasing demand for the product. In this context, it is intended to contribute with a methodology that facilitates planning for corrective, preventive and predictive maintenance, in order to improve the production process. The obtained result has revealed that it is possible to define a list of critical machines based on certain criteria, using the methodology called Hierarchical Analytical Process (AHP). It is concluded that through the simulations of unscheduled failures it is possible to carry out an analysis to obtain a list of machines with certain levels of criticality and thus improve the maintenance management of the company.